A Calculation Method for the Journal Bearing with a Determined Load Based on Response Surface Optimization. Issue 4 (3rd July 2020) - Zhang, Yu; Chen, Guoding; Wang, Lin
Abstract: Calculation with the determined load is more useful for engineering applications because the external load is easier to obtain than the bearing eccentricity. However, the calculation method based on the determined load for a journal bearing with a complex structure is still difficult to meet requirement. This article presents a calculation method to seek proper bearing eccentricity with a determined external load according to response surface methodology. The relationship between the relative eccentricity and attitude angle of the journal bearing and the external load is determined according to response surface optimization. The Navier-Stokes and elastic deformation equations are adopted during calculation of lubricating properties. The validity of the calculation method is verified with the experimental results. Moreover, the method is proved to be applicable to calculation of the fixed load based on the Reynolds equation.